Consumo de refrigerantes, estado nutricional e coocorrência de fatores de risco obesogênicos em adolescentes brasileiros: Pesquisa Nacional de Saúde do Escolar - Otaviana Cardoso Chaves (2017)
Introduction: In recent decades, there have been global changes in dietary patterns with the increased consumption of ultra-processed products, more specifically of soft drinks. The consumption of such beverages has been associated with weight gain and the emergence of metabolic changes. Thus, it is necessary to research specific national contexts to understand this practice and its relationship with nutritional status. Furthermore, inadequate dietary choices and low levels of physical activity tend to cluster. We believe that knowing the factors associated with the simultaneous occurrence of these behaviors can be an important step to prevent chronic diseases related to overweight. Objectives: This dissertation has three objectives, namely 1) to estimate the prevalence of daily consumption of sugar-sweetened soft drinks by Brazilian adolescents and to identify associated factors; 2) to evaluate cross-sectional associations between the consumption of sugar-sweetened soft drinks and body mass index (BMI) in eutrophic and overweight adolescents; and 3) to estimate the prevalence and sociodemographic and family context characteristics associated with the co-occurrence of obesogenic risk factors in adolescents. Methods: This was a cross-sectional epidemiological study based on data from the National Adolescent Student Health Survey (2009), which evaluated students from the 9th grade of the 26 Brazilian state capitals and the Federal District. Three manuscripts were produced, each referring to one of the objectives. In the first manuscript, we estimated the association between sociodemographic, family, and behavioral factors and the daily consumption of soft drinks using the prevalence ratio (PR) and respective intervals of confidence obtained by the Poisson regression. In the second manuscript, we used multinomial regression models to evaluate the association between the consumption of soft drinks and body mass index in eutrophic and overweight adolescents. In the third manuscript, the response variable was the combined presence of five potential obesogenic risk factors (daily consumption of sugar-sweetened soft drinks, daily consumption of sweets, insufficient fruit intake, insufficient vegetable intake, and physical inactivity). We identified the sociodemographic and family context variables associated with the co-occurrence of obesogenic risk behaviors using the ordinal logistic regression through the partial proportional odds model. We conducted the analyses considering the complex design of the sample, using the Stata software version 12. Results: The daily consumption of sugar-sweetened soft drinks was reported by 21.6% (95% IC: 20.8 - 22.4) of adolescents. The variables of being female, performing physical activity, and consuming milk daily had an inverse relationship with the daily consumption of soft drinks. We observed a higher prevalence of daily soft drink consumers among the older students from private schools, living in regions of higher socioeconomic status, belonging to the upper third score for goods and services, those whose guardians had less knowledge about their free time, who had the habit of eating while watching television or studying, who had more time using the computer, and who consumed daily sweets, cookies, and processed meat. We found an interaction between the consumption of these foods and soft drinks, with a gradual increase in the strength of association (article 1). Of the 57,268 adolescents included in the second article, 23.81% were overweight. In eutrophic boys, soft drink consumption was associated with a higher chance of being in the upper third BMIz when compared to non-consumers. In overweight adolescents, both male and female, the consumption of soft drinks was associated with a lower chance of being in the upper third BMIz. The third article showed that 62.79% of adolescents were exposed to three or more obesogenic risk factors, simultaneously. There was a greater chance of simultaneous occurrence of factors in female adolescents, in those with less parental monitoring, and who shared fewer meals with their guardians. In contrast, adolescents living in more developed regions of the country and those whose mothers had higher education had a lower chance of co-occurrence of obesogenic risk factors. Conclusion: We observed high frequencies in the consumption of sugar-sweetened soft drinks and a high prevalence of overweight in Brazilian adolescents. The habit of consuming the beverage daily remained associated with other unhealthy practices and potentially associated with higher categories of BMIz in eutrophic male adolescents. Furthermore, the simultaneous occurrence of obesogenic risk factors in adolescents is worth noting. Thus, prevention strategies should be based on a comprehensive approach, discouraging the consumption of ultra-processed products and relying on family involvement, which may improve the nutritional and health status of adolescents.